To the top! : climbing the world's highest mountain - Kramer, Sydelle; LaPadula, Tom (New York : Random House, 1993)
Describes how Edmund Hillary and Tenzing Norgay became the first human beings to reach the top of the world by climbing Mount Everest
2-4.
620
Accelerated Reader AR
Keywords: Tenzing Norkey, -- 1914-1986.; Hillary, Edmund, -- Sir; Mountaineers; Mountaineering -- Everest, Mount (China and Nepal) -- History